An investigation of multicultural personality traits of EFL learners in English as a medium of instruction setting: The case of Saudi Arabia - Alghizzi, Talal Musaed; Alshahrani, Tahani Munahi (Frontiers in Psychology, 2022)
Many studies have investigated the effect of multilingualism on improving personality traits, namely cultural empathy, open-mindedness, flexibility, emotional stability, and social initiative of international students, or students in an international degree program. However, few studies have examined such an issue for EFL learners as they further their academic levels in English as a Medium of Instruction (EMI) setting. The main tool used in this exploratory descriptive study was the short version (40 items) of the multicultural personality questionnaire (MPQ) that was developed by Van der Zee at al.(2013). 577 Saudi female EFL undergraduates participated voluntarily across various academic levels (1-8), as well as recently graduated students; all of whom were exposed to various amounts of EMI. Prior to the study and before administering the questionnaire, the IELTS test was used to measure language proficiency of EFL learners to make sure that the collected data of the MPQ were analyzed statistically to generate means and standard deviations. The results of ANOVA test revealed that not only did all participants improved in cultural empathy followed by‫ open-mindedness, but their improvement of the other dimensions of flexibility, social initiative, and emotional stability appeared to be randomly similar between only two or three groups of academic levels. The results also showed that there was no gradual sequence of developments or deterioration of any multicultural personality (MP) dimensions as students advanced in their academic levels or as a result of getting exposed to various amounts of EMI. Finally, this research provides some implications related to widening the scope of the study for further research such as comparing trilingual and bilingual learners and modifying the diagnostic ability of the MPQ. ‬‬‬‬‬‬‬‬‬‬‬‬‬ ‬.‬‬